Pengaruh Pemahaman Pajak, Tingkat Pendidikan, dan Sosialisasi Perpajakan terhadap Kepatuhan Pajak BUMDes (Studi pada BUMDes di Kabupaten Buleleng): Studi pada BUMDes di Kabupaten Buleleng - Sugiantara, Febry; Sinarwati, Ni Kadek (Universitas Pendidikan Ganesha, 2023)
This study aims to analyze the effect of tax understanding, education level, and tax socialization on BUMDes tax compliance in Buleleng Regency after the issuance of Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises. This type of research is quantitative research with a Likert scale questionnaire distribution method and data processed using SPSS Version 25. The population is BUMDes recorded in the Community and Village Empowerment Office of Buleleng Regency in 2023. Sampling using Purposive Sampling technique with a total sample of 63 BUMDes. Data analysis of this study used descriptive statistical analysis, data quality test, classical assumption test, and hypothesis testing. The results showed that tax understanding has a significant effect on BUMDes tax compliance, while education level and tax socialization does not have a significant effect on BUMDes tax compliance, and simultaneously tax understanding, education level, and tax socialization have a significant effect on BUMDes tax compliance.